Multiple pathways mediate the sex-peptide-regulated switch in female Drosophila reproductive behaviours. - Haussmann, I.U.; Hemani, Y.; Wijesekera, T.; Dauwalder, B.; Soller, M. (Proceedings. Biological sciences / The Royal Society., 2013)
Male-derived sex-peptide (SP) induces profound changes in the behaviour of Drosophila females, resulting in decreased receptivity to further mating and increased egg laying. SP can mediate the switch in female reproductive behaviours via a G protein-coupled receptor, SPR, in neurons expressing fruitless, doublesex and pickpocket. Whether SPR is the sole receptor and whether SP induces the postmating switch in a single pathway has not, to our knowledge been tested. Here we report that the SP response can be induced in the absence of SPR when SP is ectopically expressed in neurons or when SP, transferred by mating, can access neurons through a leaky blood brain barrier. Membrane-tethered SP can induce oviposition via doublesex, but not fruitless and pickpocket neurons in SPR mutant females. Although pickpocket and doublesex neurons rely on G(o) signalling to reduce receptivity and induce oviposition, G(o) signalling in fruitless neurons is required only to induce oviposition, but not to reduce receptivity. Our results show that SP's action in reducing receptivity and inducing oviposition can be separated in fruitless and doublesex neurons. Hence, the SP-induced postmating switch incorporates shared, but also distinct circuitry of fruitless, doublesex and pickpocket neurons and additional receptors.